Multiple Introductions of Mycobacterium tuberculosis Lineage 2–Beijing Into Africa Over Centuries - Rutaihwa, Liliana K.; Menardo, Fabrizio; Stucki, David; Gygli, Sebastian M.; Ley, Serej D.; Malla, Bijaya; Feldmann, Julia; Borrell, Sonia; Beisel, Christian; Middelkoop, Kerren; Carter, E. Jane; Diero, Lameck; et al. (Frontiers in Ecology and Evolution, 2019)
The Lineage 2–Beijing (L2–Beijing) sub-lineage of Mycobacterium tuberculosis has received much attention due to its high virulence, fast disease progression, and association with antibiotic resistance. Despite several reports of the recent emergence of L2–Beijing in Africa, no study has investigated the evolutionary history of this sub-lineage on the continent. In this study, we used whole genome sequences of 781 L2 clinical strains from 14 geographical regions globally distributed to investigate the origins and onward spread of this lineage in Africa. Our results reveal multiple introductions of L2–Beijing into Africa linked to independent bacterial populations from East- and Southeast Asia. Bayesian analyses further indicate that these introductions occurred during the past 300 years, with most of these events pre-dating the antibiotic era. Hence, the success of L2–Beijing in Africa is most likely due to its hypervirulence and high transmissibility rather than drug resistance.